1997
DOI: 10.1056/nejm199709183371202
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Clozapine and Haloperidol in Hospitalized Patients with Refractory Schizophrenia

Abstract: For patients with refractory schizophrenia and high levels of hospital use, clozapine was somewhat more effective than haloperidol and had fewer side effects and similar overall costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
181
1
7

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(198 citation statements)
references
References 23 publications
9
181
1
7
Order By: Relevance
“…Six trials , 100 Lee 1994, 114 Tamminga 1994, 102 Essock 1996, 103 Rosenheck 1997, 105 Covington 2000 69 ) were longer than 26 weeks (long term); the remainder fell into the short-term category, with a maximum length of 20 weeks.…”
Section: Durationmentioning
confidence: 99%
See 2 more Smart Citations
“…Six trials , 100 Lee 1994, 114 Tamminga 1994, 102 Essock 1996, 103 Rosenheck 1997, 105 Covington 2000 69 ) were longer than 26 weeks (long term); the remainder fell into the short-term category, with a maximum length of 20 weeks.…”
Section: Durationmentioning
confidence: 99%
“…Six further studies (Honigfeld 1984, 88 Kane 1994, 100 Kumra 1996, 104 Rosenheck 1997, 105 Howanitz 1999, 106 Blinding had been applied in most studies: 35 were reported to be double-blind and two single-blind; only three studies (Lee 1994, 101 Essock 1996, 103 Chow 2000 73 ) lacked any blinding at all.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies comparing the efficacy of clozapine with other drugs have indicated the usefulness of this atypical drug in both positive and negative symptoms of schizophrenia (Safferman et al 1991;Remington and Kapur 2000). The absence of extrapyramidal side effects (EPS) has been a significant factor in its efficacy (Rosenheck et al 1997). This unique profile of clozapine has resulted in an ongoing effort to develop drugs that have the "clozapine pharmacological profile" (Schaus and Bymaster 1998).…”
mentioning
confidence: 99%
“…We have fit HMMs to data from a comprehensive double-blind trial that compared the impact of haloperidol and clozapine, two medications for treating schizophrenia, on clinical outcomes, social, vocational and community functioning and societal costs (Rosenheck et al, 1997). This data set has already been studied using a cluster-based health state model, which will allow us to make direct comparisons between the HMM and cluster methods.…”
Section: Introductionmentioning
confidence: 99%